A novel GABAergic dysfunction in human Dravet syndrome. (11th October 2018) - Ruffolo, Gabriele; Cifelli, Pierangelo; Roseti, Cristina; Thom, Maria; van Vliet, Erwin A.; Limatola, Cristina; Aronica, Eleonora; Palma, Eleonora
Summary: Objective: Dravet syndrome is a rare neurodevelopmental disease, characterized by general cognitive impairment and severe refractory seizures. The majority of patients carry the gene mutation SCN1A, leading to a defective sodium channel that contributes to pathogenic brain excitability. A γ‐aminobutyric acid (GABAergic) impairment, as in other neurodevelopmental diseases, has been proposed as an additional mechanism, suggesting that seizures could be alleviated by GABAergic therapies. However, up to now the physiological mechanisms underlying the GABAergic dysfunction in Dravet syndrome are still unknown due to the scarce availability of this brain tissue. Here we studied, for the first time, human GABAA ‐evoked currents using cortical brain tissue from Dravet syndrome patients. Methods: We transplanted in Xenopus oocytes cell membranes obtained from brain tissues of autopsies of Dravet syndrome patients, tuberous sclerosis complex patients as a pathological comparison, and age‐matched controls. Additionally, experiments were performed on oocytes expressing human α1β2γ2 and α1β2 GABAA receptors. GABAA currents were recorded using the two‐microelectrodes voltage‐clamp technique. Quantitative real‐time polymerase chain reaction, immunohistochemistry, and double‐labeling techniques were carried out on the same tissue samples. Results: We found (1) a decrease in GABA sensitivity in Dravet syndrome compared to controls, which was related to an increase in α4‐ relative to α1‐containing GABAA receptors; (2) a shift of the GABA reversal potential toward more depolarizing values in Dravet syndrome, and a parallel increase of the chloride transporters NKCC1/KCC2 expression ratio; (3) an increase of GABAA currents induced by low doses of cannabidiol both in Dravet syndrome and tuberous sclerosis complex comparable to that induced by a classical benzodiazepine, flunitrazepam, that still persists in γ‐less GABAA receptors. Significance: Our study indicates that a dysfunction of the GABAergic system, considered as a feature of brain immaturity, together with defective sodium channels, can contribute to a general reduction of inhibitory efficacy in Dravet brain, suggesting that GABAA receptors could be a target for new therapies.